Development of a multiplex fluorescent qPCR assay for the simultaneous detection of bovine viral diarrhea virus and pathogenic Escherichia coli - Wenxin Zhu; Huanxing Zhu (PLoS ONE, 2026)
Neonatal calf diarrhea, primarily caused by bovine viral diarrhea virus (BVDV) and enterotoxigenic Escherichia coli K99, poses a significant threat to the cattle industry. This study aimed to develop a multiplex qPCR assay for the simultaneous detection of both pathogens. We established specific primers and probes and generated optimized qPCR standard curves, achieving high analytical sensitivity, with limits of detection of 10² copies/μL for the BVDV target fragment and 10¹ copies/μL for the E. coli K99 plasmid DNA, without cross-reactivity with other bovine pathogens. The assay demonstrated good repeatability and was validated using clinical samples, confirming its effectiveness for accurate diagnostics. This multiplex qPCR assay enhances monitoring of BVDV and E. coli infections in livestock, potentially reducing economic losses from outbreaks.